Performance trade-offs and ageing in the `world's greatest athletes` - Careau, V.; Wilson, R. S. (Proceedings of the Royal Society B, 2017)
The mechanistic foundations of performance trade-offs are clear: because body size and shape constrains movement, and muscles vary in strength and fibre type, certain physical traits should act in opposition with others (e.g. sprint versus endurance). Yet performance trade-offs are rarely detected, and traits are often positively correlated. A potential resolution to this conundrum is that within-individual performance trade-offs can be masked by among-individual variation in `quality`. Although there is a current debate on how to unambiguously define and account for quality, no previous studies have partitioned trait correlations at the within- and among-individual levels. Here, we evaluate performance trade-offs among and within 1369 elite athletes that performed in a total of 6418 combined-events competitions (decathlon and heptathlon). Controlling for age, experience and wind conditions, we detected strong trade-offs between groups of functionally similar events (throwing versus jumping versus running) occurring at the among-individual level. We further modelled individual (co)variation in age-related plasticity of performance and found previously unseen trade-offs in throwing versus running performance that manifest through ageing. Our results verify that human performance is limited by fundamental genetic, environmental and ageing constraints that preclude the simultaneous improvement of performance in multiple dimensions. Identifying these constraints is fundamental to understanding performance trade-offs and predicting the ageing of motor function. Footnotes